Exosomes derived from miR-301a-3p-overexpressing adipose-derived mesenchymal stem cells reverse hypoxia-induced erectile dysfunction in rat models - Li Liang; Dachao Zheng; Chao Lu; Qinghong Xi; Hua Bao; Wengfeng Li; Yufei Gu; Yuanshen Mao; Bin Xu; Xin Gu (Stem Cell Research & Therapy, 2021)
Abstract Background Erectile dysfunction (ED) has often been observed in patients with obstructive sleep apnea (OSA). Research on adipose-derived mesenchymal stem cell (ADSC)-derived exosomes has shown that they have significant therapeutic effects in many diseases including ED. Methods In this study, ED was induced in Sprague Dawley (SD) rats using chronic intermittent hypoxia (CIH) exposure. CIH-mediated influences were then measured in the corpus cavernous smooth muscle cells (CCSMCs). Results Our data showed that miR-301a-3p-enriched exosome treatment significantly recovered erectile function in rats and CCSMCs by promoting autophagy and inhibiting apoptosis. The treatment also significantly recovered the level of alpha smooth muscle actin (α-SMA) in rats and CCSMCs. Bioinformatics predicted that phosphatase and tensin homolog (PTEN) and Toll-like receptor 4 (TLR4) might be targets of miR-301a-3p. Conclusions Our results indicate that PTEN-overexpression vectors or TLR4-overexpression vectors reverse the therapeutic effects achieved by miR-301a-3p in CCSMCs indicating that PTEN/hypoxia-inducible factor-1 alpha (HIF-1α) and TLR4 signaling pathways play key roles in the progression of ED. The findings in this study suggest that miR-301a-3p should be considered a new therapeutic target for treating ED associated with OSA.